Characteristics of Beef Packed in a Plastic Bag Vacuum (Vacuum Pack) - I Gede Putu (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2001)
Development of vacuum packaging teknology on beef production in Indonesia has been started since 1990’s by meat packer industry. The application of vacuum pack technology give advantage for both producer and customer. The advantage for producer is the ability to maintain the shelf life of the products, prevent cross contamination and improve meat quality or tenderness due to ageing process. While from the customer point of view, the packaging technology is an assurance for quality and wholesomeness of the products to be consumed. The vacuum pack technology have been applied mainly for imported prime beef required by hotel and restaurants. However, for most of the customers in Indonesia, the vacuum pack technology for fresh chilled beef has not been well recognized. Therefore, it is important to present a complete information on mechanism and characteristic of vacuum packed chilled beef in order to improve preference in utilising vacuum packed technology.